Morphological and Transcriptomic Analysis Reveals the Osmoadaptive Response of Endophytic Fungus Aspergillus montevidensis ZYD4 to High Salt Stress - Liu, Kai-Hui; Ding, Xiao-Wei; Narsing Rao, Manik Prabhu; Zhang, Bo; Zhang, Yong-Gui; Liu, Fei-Hu; Liu, Bing-Bing; Xiao, Min; Li, Wen-Jun (Frontiers in Microbiology, 2017)
Halophilic fungi have evolved unique osmoadaptive strategies, enabling them to thrive in hypersaline habitats. Here, we conduct morphological and transcriptomic response ofendophytic fungus (AspergillusmontevidensisZYD4) in both the presence and absence of salt stress. Under salt stress, the colony morphology of theA. montevidensisZYD4 changed drastically and exhibited decreased colony pigmentation. Extensive conidiophores development was observed under salt stress; conidiophores rarely developed in the absence of salt stress. Under salt stress, yellow cleistothecium formation was inhibited, while glycerol and compatible sugars continued to accumulate. Among differentially expressed unigenes (DEGs), 733 of them were up-regulated while 1619 unigenes were down-regulated. We discovered that genes involved in the accumulation of glycerol, the storage of compatible sugars, organic acids, pigment production, and asexual sporulationwere differentially regulated under salt stress. These results provide further understanding of the molecular basis of osmoadaptive mechanisms of halophilic endophytic fungi.